INDONESIA MENGHADAPI COVID-19; REALITAS BERGEREJA DITENGAH PANDEMI GLOBAL - Imelda Ch Pocerattu (TANGKOLEH PUTAI, 2021)
The global world at the end of 2019 was shocked by the pandemic caused by the Corona Virus. Until now the case of COVID-19 (coronavirus) has become a global pandemic, especially in Indonesia. Large-scale social restrictions are the impact of the ongoing spread of the corona virus (Covid-19). Corona Virus Disease 2019 (Covid-19) is causing global concern because of its very fast and deadly spread. The government is promoting social distancing/physical distancing policies, reducing crowds to minimize the development of Covid-19. The Indonesian people accepted the recommendation but there were several reactions such as panic buying, persecution of health workers who were assumed to be exposed to Covid-19. Government regulations have restricted social gatherings, both in public places and in churches. Finally, worship was held in their respective homes online using internet-based technology to carry out worship in order to break the chain of the spread of this virus.